2018
DOI: 10.1007/s10270-018-0698-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating user interface generation approaches: model-based versus model-driven development

Abstract: Advances in software design possibilities have led to a growing interest in the study of User Interfaces (UIs). Many Model-Based User Interface Development Environments (MB-UIDEs) have been proposed to deal with the generation of the UIs (semi) automatically by using models with different levels of abstraction. Often, this generation is limited to the UI-part of an application. However, achieving true model-driven development (MDD) requires the co-development of application and user interface and hence needs t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 55 publications
0
6
0
1
Order By: Relevance
“…Still, it is dedicated to Python and oriented with a template design system to render them, so it does not face the same issues as SPA. No solution provides the automated functionality of sophisticated analysis with data filtering based on custom conditions with automatically generated filter forms [28,48] and data table rendering. Besides GUI enhancements, NEFBDAA gives pre-configured and built upon the best design patterns environment for building web-based applications utilizing the SPA approach.…”
Section: Scientific and Technological Contextmentioning
confidence: 99%
“…Still, it is dedicated to Python and oriented with a template design system to render them, so it does not face the same issues as SPA. No solution provides the automated functionality of sophisticated analysis with data filtering based on custom conditions with automatically generated filter forms [28,48] and data table rendering. Besides GUI enhancements, NEFBDAA gives pre-configured and built upon the best design patterns environment for building web-based applications utilizing the SPA approach.…”
Section: Scientific and Technological Contextmentioning
confidence: 99%
“…There are studies regarding the usability of modelling languages that are usually used to design systems or the usability of a tool itself regarding the user interfaces (e.g. [43]). Since the GTT approach aims at a formal specification, some works focussing on the evaluation of specification languages are stated here.…”
Section: Usability Study Of Specification Languagesmentioning
confidence: 99%
“…This type of contribution is particularly welcome since EICS has accumulated considerable knowledge, which is now in the need of consolidation. A recent survey [22] of EICS approaches revealed that the pool of entries is large and challenging.…”
Section: A Submitter's Guide To Engineering Interactive Computing Systemsmentioning
confidence: 99%